Cultural Genocide and the Protection of Cultural Heritage - Luck, Edward C.; Project Muse; J. Paul Getty Trust; Project Muse. (Project Muse, 2020)
Cultural Genocide and the Protection of Cultural Heritage examines the various lenses through which the international community defines attacks on cultural heritage--legal, accountability, security, counterterrorism, and atrocity prevention--and proposes a sixth, cultural genocide, that can be used to recast the debate over how to best protect the world's cultural heritage.
Issued as part of book collections on Project MUSE.
Includes bibliographical references.
Description based on print version record.
Keywords: Art and war; Art treasures in war; Architecture -- Conservation and restoration; Art -- Conservation and restoration; Cultural property -- Protection; Electronic books; Electronic books